2011
DOI: 10.2106/jbjs.i.01763
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Bone Morphogenetic Protein-2: A Randomized Trial in Open Tibial Fractures Treated with Reamed Nail Fixation

Abstract: The healing of open tibial fractures treated with reamed intramedullary nail fixation was not significantly accelerated by the addition of an absorbable collagen sponge containing rhBMP-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
100
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(102 citation statements)
references
References 19 publications
1
100
1
Order By: Relevance
“…Recombinant human BMP-2 protein has been clinically used to enhance bone healing 18,27,28 Although our study did not find a significant difference in TGF-β1 or BMP-2 levels between normal union and nonunion groups which is consistent with previously reported findings, however we found a delayed maximal peak for both TGF-β1 and BMP-2 proteins in nonunion patients as compared to the normal union patients. The peak plasma value of TGF-β1 at 2-week may be explained by the fact that TGF-β1 is released from the granules of platelets during the clotting process soon after trauma 31 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Recombinant human BMP-2 protein has been clinically used to enhance bone healing 18,27,28 Although our study did not find a significant difference in TGF-β1 or BMP-2 levels between normal union and nonunion groups which is consistent with previously reported findings, however we found a delayed maximal peak for both TGF-β1 and BMP-2 proteins in nonunion patients as compared to the normal union patients. The peak plasma value of TGF-β1 at 2-week may be explained by the fact that TGF-β1 is released from the granules of platelets during the clotting process soon after trauma 31 .…”
Section: Discussionsupporting
confidence: 92%
“…Also, the expressions of type IIB relative to type IIA procollagens and alpha 10 relative to alpha 11 integrin subunits were found to be good markers of chondrocytes differentiation state 16 . BMP-2 deficiency has been implicated in the delayed union or nonunion and recombinant BMP-2 and BMP-7 have been clinically used in the treatment of delayed union or nonunion 15,17,18 . In addition a possibility of involvement of a BMP-related genetic predisposition in impaired fracture healing has been reported 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Govender et al [8] evaluated rhBMP-2 in patients with open tibial shaft fractures and found a large reduction in the need for secondary procedures. Aro et al [1] conducted a subsequent RCT in a similar population and found no difference in secondary procedures. Aro et al [1] postulated that the difference was attributable to the type of nailing: the first trial included a majority of patients treated with unreamed nailing whereas the subsequent trial was restricted to patients with reamed nailing.…”
Section: Are the Results Of Individual Studies In The Direct Comparismentioning
confidence: 99%
“…Aro et al [1] conducted a subsequent RCT in a similar population and found no difference in secondary procedures. Aro et al [1] postulated that the difference was attributable to the type of nailing: the first trial included a majority of patients treated with unreamed nailing whereas the subsequent trial was restricted to patients with reamed nailing. In the trial by Govender et al [8], benefit was restricted to patients who had undergone unreamed nailing and the subsequent trial was conducted to clarify the effect in patients undergoing reamed nailing (and it confirmed the lack of benefit seen in in the initial trial).…”
Section: Are the Results Of Individual Studies In The Direct Comparismentioning
confidence: 99%
“…BMPs are thought to initiate fracture healing, but they have obvious side effects such as local swelling, pain, and increased risk of wound infections (Aro et al 2011, Carragee et al 2011). Studies sponsored by industry have obviously not reported the adverse effects associated with the administration of BMPs in spinal fusion (Carragee et al 2011).…”
mentioning
confidence: 99%